2015
DOI: 10.1542/peds.2014-1550
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the Tension Between Hyperoxia Prevention and Alarm Fatigue in the NICU

Abstract: BACKGROUND: After the implementation of narrowed oxygen saturation alarms, alarm frequency increased in the C.S. Mott Children's Hospital NICU which could have a negative impact on patient safety. The Joint Commission on the Accreditation of Healthcare Organizations issued a Sentinel Event Alert for hospitals in 2013 to improve alarm safety, resulting in a 2014 National Patient Safety Goal requiring institutional policies and procedures to be in place to manage alarms.METHODS: A multidisciplinary improvement t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 23 publications
1
33
0
1
Order By: Relevance
“…It has been reported that a narrower TR leads to an inevitable increase of SpO 2 alarms 17. These alarms contribute to all other alarms on a NICU where a high number of alarms are false 18.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that a narrower TR leads to an inevitable increase of SpO 2 alarms 17. These alarms contribute to all other alarms on a NICU where a high number of alarms are false 18.…”
Section: Discussionmentioning
confidence: 96%
“…Partnering with stakeholders such as clinical leadership, bedside providers and technical staff was critical. Our approach incorporated many evidence-based interventions previously shown to reduce alarm notifications,19 such as implementing alarm delays,20 changing ECG electrodes daily11 and generating algorithms for alarm notification 21 22. Previously, these strategies successfully decreased the number of alarms per patient-day over fourfold without compromising patient safety 11 23.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing staff satisfaction was prioritised as an outcome given evidence that reducing non-actionable alarm frequency is associated with improved nursing satisfaction and morale 22. A decrease in alarm notifications can also help reduce nursing’s perceived workload and improve work environment satisfaction 26 27.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of measures of impact on the management of SpO2, HR and STS alarms already recommended in the literature is of utmost importance, such as the preparation of the skin for the adhesion of electrodes, their replacement in an appropriate period (within 24 hours), the use of an oximetry reading device with good end-to-end adaptation, disabling oximetry in patients with poor peripheral perfusion, correct ST-segment alarm configuration, daily monitoring of the soundness of monitoring cables, adjusting the gain of the R wave and the need to apply short delays of some alarms, especially those of SpO2 (25,26) .…”
Section: Discussionmentioning
confidence: 99%